Mental Health and You: A Brief Annotated Bibliography. Issue 2 (3rd April 2022) - Phillips, Kat
Abstract: Mental health is a pinnacle aspect of one's overall well-being, both emotionally and physically. This column takes a look at mental health resources for the general or adult population and the youth population, and also identifies several reliable podcasts addressing mental health from a variety of perspectives. This brief annotated bibliography of resources is meant to serve as a starting point, not as an all-inclusive list of information. Its purpose is to aid in de-stigmatizing conversations about mental health and wellness, direct folks to some of the safe spaces to have these conversations, and provide starting points for those seeking advice or answers.